Design, synthesis and SAR of a novel series of heterocyclic phenylpropanoic acids as GPR120 agonists. Issue 15 (1st August 2017) - Zhang, Xuqing; Cai, Chaozhong; Winters, Michael; Wells, Michele; Wall, Mark; Lanter, James; Sui, Zhihua; Ma, Jingyuan; Novack, Aaron; Nashashibi, Imad; Wang, Yuanping; Yan, Wen; et al.
Graphical abstract: A novel series of 5-membered heterocycle-containing phenylpropanoic acid derivatives (I ) was discovered as potent GPR120 agonists with low clearance, high oral bioavailability and in vivo antidiabetic activity in rodents. Abstract: A novel series of 5-membered heterocycle-containing phenylpropanoic acid derivatives was discovered as potent GPR120 agonists with low clearance, high oral bioavailability and in vivo antidiabetic activity in rodents.